Transports of Delight : an Aromatic Journey in Verse from East to West on the Wings of Perfume. (BRILL, 2007)
This book is a celebration through verse of man's extraordinary sensory world of smell, connecting East and West. Here is a fascinating and delightful anthology, drawn from around the world and across the millennia, capturing a kaleidoscope of emotions, moods and memories, all of which are energized and enhanced by smells of every kind.